STREAMING SELVES: VULGAR LANGUAGE, CODE-MIXING, AND HYBRID COMMUNAL IDENTITY OF AN INDONESIAN LIVE-STREAMER - Fariq Shiddiq Tasaufy; Cicilia Deandra Maya Putri; Slamet Setiawan; Ayunita Leliana; Lina Purwaning Hartanti; Imam Hanafi; Noerhayati Ika Putri (LiNGUA: Jurnal Ilmu Bahasa dan Sastra, 2025)
This paper examines how an Indonesian live-streamer and his audiences create a hybrid communal identity by using vulgar language and code-mixing with reference to the popular YouTube livestream @deandeankt. With the digital medium transforming the world into a global village, the streaming culture in Indonesia provides a distinct perspective into how localized linguistic practices interact with global trends in the internet. The interpretivist-constructivist paradigm applied in the current case study research was aimed at understanding the way language and interaction produced hybrid identities. It gathered linguistic and paralinguistic data of @deadndeakt’s livestream for 90 minutes with netnography and thematic analyses. According to the study, abusive swearing (e.g., "kontol [dick]", "goblok [stupid]") represents 89.3 percent of the vulgar language and serves as playful insults, which enhance group cohesion. Emphatic swearing ("Anjing! Gua kalah! [Bitch! I lost!]") and cathartic swearing (“Ngentot, mic-nya rusak! [Fuck, the microphone is broken!]”) increase the emotional involvement. Intra-sentential blends, especially code-mixing (“Brightness-nya kita bikin tiga kali [We increase the brightness threefold]”), prevails in 85 percent. Other examples combine English gaming slang (template, unarchive) with Indonesian structure and local dialects, like a Javanese swear word (“Cok [Damn]”). Pronunciations, such as BTW [read in Indonesian: be te we] are even more localized global terms. It is analyzed that the vulgar language usage assists in persona creation and building of relationships with the audience, creating a tight-knit, exclusive community in which such language represents belonging and emotional release, despite its offensiveness in the larger society. Moreover, streamers combine Indonesian and English with gaming jargon to successfully appeal to their bilingual audience, so that they could be technically accurate and still fit into the global gaming cultures. These activities form a hybrid identity, where speakers possess a strong sense of Indonesian culture but are consistent with international trends, which strengthens group exclusivity. The results draw attention to live-streaming as a contact zone in which language negotiates belonging, which disrupts strict cultural boundaries. The study highlights the sociolinguistic innovativeness of online communities and recommends future research on offline effects of these online linguistic norms and the effects of the hybrid identities and communicative practices used in live-streaming communities on daily language, social interaction, and identity formation in the real world. The authors also suggest cross-cultural comparative research to find out whether the phenomena are specific to the Indonesian situation or have they become a global trend.